Investigation of the mechanism of chatter formation during metal cutting process - Amin, A. K. M. Nurul (1983)
Experiments have been carried out to determine the physical nature and characteristics of the unstability of metal cutting process for different pairs of work and tool materials and their influence on chatter formation. Also the influence of the characteristics of various parameters of the elastic system of machine-tools and conditions of machining on chatter have been considered. Experimental results enabled the discovery of the mechanism of stable cutting conditions.